1978
DOI: 10.3382/ps.0571355
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dietary Protein Level on Productive Performance and Egg Quality of Four Strains of White Leghorn Hens

Abstract: The effects of a mid-laying period reduction in dietary protein level on productive performance was studied with 576 individually caged Single Comb White Leghorn hens from four strains. The hens on treatments 1 and 2 received diets that contained by calculation 17 and 15% protein, respectively, between 143 and 507 days of age, while those on treatment 3 received 17 and 13% protein diets from 143 to 325 and 326 and 507 days, respectively. For treatment 4, diets containing 15 and 13% protein were given during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
1

Year Published

1980
1980
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 7 publications
(7 reference statements)
4
9
0
1
Order By: Relevance
“…These results agree with those reported by Hamilton et al (1979), but earlier Gowe (1977) and Hamilton (1978b) reported significant differences in albumen quality expressed as Haugh units. Generally, there was little evidence of effects on the egg from changes in the (Na+K)/Cl ratio.…”
Section: Resultssupporting
confidence: 95%
“…These results agree with those reported by Hamilton et al (1979), but earlier Gowe (1977) and Hamilton (1978b) reported significant differences in albumen quality expressed as Haugh units. Generally, there was little evidence of effects on the egg from changes in the (Na+K)/Cl ratio.…”
Section: Resultssupporting
confidence: 95%
“…The absence of any major genotype-protein level interaction in this study is in agreement with recent results of Hamilton (1978) but in contrast to results published by Deaton and Quisenberry (1965) for 14% to 17% protein rations and four egg production stocks; by Moreng et al (1964) for 13 to 17% protein and four commercial egg stocks; and by Harms et al (1966) for 11% to 17% protein and six stocks. In the last study, the interaction involved either the one meat line or ration protein levels outside the range of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…The results of Deaton and Quisenberry (1965) are difficult to compare with those of the present study because the two rations they used each involved changes in protein level during the laying period. The lack of strain x protein level interaction in Hamilton's (1978) report may be explained by the small direct effects of either strain or protein levels on performance. Moreng et al (1964) concluded that their interaction was probably due to the failure of one strain to assimilate sufficient quantities of at least one amino acid.…”
Section: Discussionmentioning
confidence: 72%
“…Researchers found no changes in Haugh units in the early phase (20-43 weeks of age) of the production cycle when feeding low protein diets (Novak et al, 2006;Deaton and Quisenberry, 1965;Aitken et al, 1973;and Leeson and Caston, 1997). On the other hand, Hamilton (1978) observed no clear change in Haugh units when feeding low protein diets to 4 different strains of laying hens.…”
Section: Discussionmentioning
confidence: 86%